2016
DOI: 10.1556/2006.5.2016.076
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between study addiction and work addiction: A cross-cultural longitudinal study

Abstract: AimsRecent empirical studies investigating “study addiction” have conceptualized it as a behavioral addiction, defined within the framework of work addiction. This study is the first attempt to examine the longitudinal relationship between study addiction and work addiction.MethodsThe Bergen Study Addiction Scale (BStAS), the Bergen Work Addiction Scale (BWAS), and the Ten-Item Personality Inventory were administered online together with questions concerning demographics and study-related variables in two wave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
45
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 26 publications
9
45
0
1
Order By: Relevance
“…Respondents provided answers on a 7-point Likert scale, ranging from disagree strongly (1) to agree strongly (7). The TIPI has shown good validity and reliability in previous studies (Atroszko 2015;Atroszko et al 2016aAtroszko et al , 2016bAtroszko et al 2018). In the present study the Spearman-Brown reliability coefficient was of .74 for Extraversion, .29 for Agreeableness, .72 for Conscientiousness, .62 for Emotional stability and .35 for Openness, respectively.…”
Section: Instrumentssupporting
confidence: 76%
“…Respondents provided answers on a 7-point Likert scale, ranging from disagree strongly (1) to agree strongly (7). The TIPI has shown good validity and reliability in previous studies (Atroszko 2015;Atroszko et al 2016aAtroszko et al , 2016bAtroszko et al 2018). In the present study the Spearman-Brown reliability coefficient was of .74 for Extraversion, .29 for Agreeableness, .72 for Conscientiousness, .62 for Emotional stability and .35 for Openness, respectively.…”
Section: Instrumentssupporting
confidence: 76%
“…Respondents provided answers on a 7-point Likert scale, ranging from 1 (disagree strongly) to 7 (agree strongly). The TIPI has shown good validity and reliability in previous studies (Atroszko, 2015;Atroszko, Andreassen, Griffiths, & Pallesen, 2016a, 2016bAtroszko et al, 2018). In the presented sample, the Spearman-Brown reliability coefficient was .66 for Extraversion, .43 for Agreeableness, .67 for Conscientiousness, .68 for Neuroticism and .30 for Openness to experience.…”
Section: Methodssupporting
confidence: 68%
“…The Likert-type response scale ranged from 1 (never) to 5 (always). The scale has demonstrated good construct validity and reliability in previous studies (Atroszko, 2015;Atroszko et al, 2015Atroszko et al, , 2016aAtroszko et al, 2019b;Lawendowski et al, 2019). In the present study, single-factor structure was confirmed in the Polish sample (MLR estimator, χ 2 (14) = 90.19, p < .001, RMSEA = .070, 90% CI RMSEA = .056-.084, CFI = .945, SRMR = .031) as well as in Indian sample (MLR estimator, error terms of items 1 and 2 cor-related, χ 2 (13) = 23.35, p = .038, RMSEA = .052, 90% CI RMSEA = .012-.086, CFI = .927, SRMR = .046).…”
Section: Methodsmentioning
confidence: 72%
“…This problematic studyrelated behaviour can have varying intensity from mild to severe" (Atroszko, Demetrovics, & Griffiths, 2019, p. 9). Study addiction was shown to be related to work addiction in longitudinal research (Atroszko, Andreassen, Griffiths, & Pallesen, 2016a) and showed similar temporal stability to work addiction (Atroszko, Andreassen, Griffiths, & Pallesen, 2016b). Both addictions show seven core addiction symptoms: salience, mood modification, tolerance, withdrawal, conflict, relapse, and problems (Atroszko et al, 2015).…”
Section: Introductionmentioning
confidence: 91%